Solitary Osteochondroma of Posterior Elements of the Spine: A Rare Case Report - Pawar, Eknath (J Orthop Case Rep, 2020)
INTRODUCTION: Osteochondromas are the most common benign tumors of the bone accounting for 35% to 40% of all benign bone tumors. They present in two distinct clinical forms – solitary osteochondroma and multiple osteochondromas. Solitary osteochondroma accounts for 85% of all osteochondroma and is commonly seen in childhood and adolescence. They more frequently affect the appendicular skeleton and are rarely found in spine. Biopsy and imaging help in diagnosis and en bloc resection is the treatment of choice in symptomatic patients. CASE REPORT: We present a case of a 6-year-old girl who presented with swelling over back for 4 years. Radiological evaluation and biopsy were done and the patient was diagnosed with osteochondroma of the left lamina and spinous process of dorsal 12th vertebral body which was managed with extraperiosteal en bloc excision. CONCLUSION: Osteochondroma of the lamina and spinous process of vertebrae is rare and can be effectively treated by extraperiosteal en bloc resection and has a good post-operative outcome.